The Role of Hydrogeology Cycles in Formation Meleorative Enviroments in Kur-Araz Depression - Ibrahimova, S.I.; Ceferova, E.N.; Aghamaliyeva, G.K. (Herald of Azerbaijan Engineering Academy, 2025)
The intensity of water exchange between confined aquifers is determined by the combined interaction of litho-structural factors, oro-hydrographic and tectonic features of the territory. The intensity of water exchange is closely related to the permeability of the impermeable layer. The latter varies within the lowland from 0.0004 to 0.13 m/day, decreasing with the immersion of the impermeable layer. The rate of ascending filtration under river valleys is 1.3-1.8 times higher than the rate of descending filtration within watershed spaces.